Assistance in Bumdes Financial Management in Strengthening Village Agricultural Potential - Futri; Darmawan; Fatimah; Elva Tiara; Fitriyani Syukri (www.amertainstitute.com, 2025)
This community service project in Tangru Village, Enrekang Regency, aimed to strengthen the financial management capacity of Village-Owned Enterprises (BUMDes) and optimize the village's agricultural potential, particularly in shallot cultivation. The program involved outreach, technical counseling on cultivation practices, development of BUMDes products such as eco-friendly pesticides, and training in financial management and basic marketing strategies. A mixed-methods approach combining qualitative and quantitative data was used, including observation, interviews, and documentation. The results showed a notable improvement in farmers’ knowledge and practices related to shallot cultivation and enhanced accuracy in BUMDes financial records. These findings reflect increased community awareness of sustainable agricultural practices and financial governance. However, gaps remain in advanced accounting skills and effective marketing strategies, suggesting the need for further training and support. This program demonstrates that integrated community empowerment efforts can build foundational capacity, but sustained follow-up is essential to ensure long-term impact and institutional sustainability.